The Importance of Halal Tourism Policy in West Sumatera - Waryono Waryono (UIN Raden Mas Said Surakarta, 2022)
The rapid development of halal tourism is a huge opportunity for West Sumatra . The community is predominantly Muslim, and the socio-cultural system of life based on Islam is very strong in this area. The policy for implementing halal tourism in West Sumatra has been regulated in a Regional Regulation which was ratified in 2020. This paper aims to describe the importance of the policy for implementing halal tourism in West Sumatra. The method used is library research. The data analysis technique uses interactive analysis which consists of data collection, data presentation, data reduction and drawing conclusions. The policy for the implementation of halal tourism in West Sumatra aims to serve as a guideline in ensuring legal certainty for the implementation of regional halal tourism. Tourists who visit tourist objects become safe, comfortable, and guaranteed their health because they consume halal and safe products. With Islamic values that exist in halal tourism, it is not only beneficial for the tourism industry but also beneficial for the community in increasing faith, becoming a better human being and preventing things that are harmful to society.